2021
DOI: 10.1108/jhti-07-2021-0166
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of green organizational citizenship on the relationship between green transformational leadership and green creativity: evidence from hotels

Abstract: PurposeAwareness of environmental and environmental ethical behaviours are increasing day by day in the hospitality sector. Concepts are examined more and more from the “green” point of view. This study aims to reveal the impact of green transformational leadership on green creativity and the mediating effects of green organizational citizenship behaviours in the relationship between green transformational leadership and green creativity in the context of hospitality.Design/methodology/approachThis study was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 78 publications
1
28
0
Order By: Relevance
“…Another research conducted with tour operators in the same country denoted that green self-efficacy and harmonious environmental passion mediated the impact of green entrepreneurial orientation on green creative behavior (Luu, 2021). The findings of a study by Ogretmenoglu et al (2021) illustrated that green organizational citizenship behavior mediated the association between green transformational leadership and green creativity among hotel employees in Turkey. A study conducted in China demonstrated that hotel employees’ perceived task performance identified themselves with the company and therefore displayed high levels of PEBs (Peng et al , 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
“…Another research conducted with tour operators in the same country denoted that green self-efficacy and harmonious environmental passion mediated the impact of green entrepreneurial orientation on green creative behavior (Luu, 2021). The findings of a study by Ogretmenoglu et al (2021) illustrated that green organizational citizenship behavior mediated the association between green transformational leadership and green creativity among hotel employees in Turkey. A study conducted in China demonstrated that hotel employees’ perceived task performance identified themselves with the company and therefore displayed high levels of PEBs (Peng et al , 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 95%
“…This finding agrees with the AMO theory principles, whereby the transformational leaders’ practices in an organization aim to attract, motivate, reward, and sustain employee job behaviors toward achieving goals and objectives in environmental management through boosting OCBE behaviors and green innovation for superior green performance [ 23 , 62 ]. In addition, according to the social exchange theory, ETL may effectively drive employees to enact OCBE behaviors [ 11 ]. The results also showed that the OCBE positively affects GI.…”
Section: Discussionmentioning
confidence: 99%
“…By directly expressing care, confidence, and support to followers, transformational leadership can foster a high-quality reciprocal relationship [ 32 ]. Therefore, according to the social exchange theory, ETL may effectively motivate and stimulate subordinates to display OCBE behaviors [ 11 ]. Consequently, we can hypothesize the following:…”
Section: Theoretical Context and Hypotheses Formationmentioning
confidence: 99%
See 2 more Smart Citations